Both clades of the epidemic KPC-producing Klebsiella pneumoniae clone ST258 share a modified galactan O-antigen type - Szijártó, Valéria; Guachalla, Luis Miguel; Hartl, Katharina; Varga, Cecília; Banerjee, Pallavi; Stojkovic, Katarina; Kaszowska, Marta; Nagy, Eszter; Lukasiewicz, Jolanta; Nagy, Gábor (International journal of medical microbiology, 2016)
Klebsiella pneumoniae ST258 is a globally disseminated, extremely drug resistant, nosocomial clone with limited treatment options. We show that the vast majority of ST258 isolates express modified d-galactan-I lipopolysaccharide O-antigen, termed hereinafter as d-galactan-III. The genetic determinant required for galactan-III synthesis was identified as a distinct operon adjacent to the rfb (wb) locus encoding d-galactan-I synthesis. The three genes within the operon encode predicted glycosyltransferases. Testing an isogenic transformant pair revealed that expression of d-galactan-III, in comparison to d-galactan-I, conferred improved survival in the presence of human serum. Eighty-three percent of the more than 200 ST258 draft genome sequences currently available carries the corresponding operon and hence these isolates are predicted to express galactan-III antigens. A d-galactan-III specific monoclonal antibody (mAb) was shown to bind to extracted LPS from a panel of ST258 isolates. The same mAb confirmed accessibility of galactan-III in surface staining of ST258 irrespective of the distinct capsular antigens expressed by both clades described previously. Based on these data, the galactan-III antigen may represent an attractive target for active and passive immunization approaches against K. pneumoniae ST258.